2007
DOI: 10.1364/oe.15.011952
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-sensitive surface absorption spectroscopy using sub-wavelength diameter optical fibers

Abstract: The guided modes of sub-wavelength diameter air-clad optical fibers exhibit a pronounced evanescent field. The absorption of particles on the fiber surface is therefore readily detected via the fiber transmission. We show that the resulting absorption for a given surface coverage can be orders of magnitude higher than for conventional surface spectroscopy. As a demonstration, we present measurements on sub-monolayers of 3,4,9,10-perylene-tetracarboxylic dianhydride (PTCDA) molecules at ambient conditions, reve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(90 citation statements)
references
References 16 publications
2
86
0
Order By: Relevance
“…These fibers are referred to as microfibers. Optical microfibers are proposed as building blocks for micro-optical devices having applications in photonics, physics, chemistry, and biology [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Important advantages of microfibers are the potential for compact assembly in three dimensions, possibility of strong coupling to the environment and/or localization of radiation, and low transmission loss.…”
Section: Optical Microfibers With the Radius Of The Order Of 100 Nm-1 μMmentioning
confidence: 99%
“…These fibers are referred to as microfibers. Optical microfibers are proposed as building blocks for micro-optical devices having applications in photonics, physics, chemistry, and biology [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Important advantages of microfibers are the potential for compact assembly in three dimensions, possibility of strong coupling to the environment and/or localization of radiation, and low transmission loss.…”
Section: Optical Microfibers With the Radius Of The Order Of 100 Nm-1 μMmentioning
confidence: 99%
“…This flame brushing method allows us to reliably produce ONFs with controllable taper geometries and uniform waists. With our setup the waist can vary in length from 1 to 100 mm, and we can achieve radii as small as 150 nanometers Bilodeau et al (1988); Birks and Li (1992); Warken et al (2007); Warken (2007); Garcia-Fernandez et al (2011). Rather than sweep the flame back and forth over the fiber, we keep the flame stationary while sweeping the motors; this action reduces air currents, which could lead to nonuniformities on the fiber waist.…”
Section: Fabrication and Characterizationmentioning
confidence: 99%
“…In 2007, based on nanoparticleinduced Rayleigh-Gans scattering in a waveguiding MNF, Wang et al calculated the possibility of detection single nanoparticles adsorbed on the surface of an MNF, and showed that, by optimizing the wavelength of the probing light and the diameter of the MNF, nanoparticle-induced scattering intensity can reach detectable level with possibilities for single-molecule detection [26]. In 2007, relying on absorption of molecules adsorbed on the surface of a 500-nm-diameter MNF, Warken et al reported an ultrasensitive molecular sensor that was possible to detect sub-monolayers of 3,4,9,10-perylene-tetracarboxylic dianhydride (PTCDA) molecules at ambient conditions [27]. In 2011, by integrating a 900-nm-diameter MNF into a 125-μm-wide microfluidic channel, Zhang et al demonstrated a MNF sensor for chemical and biological applications ( Figure 16A-E) [32].…”
Section: Mnf Sensorsmentioning
confidence: 99%
“…(2) Strong evanescent field Strong evanescent field offers strong near-field interaction between the MNF and its surroundings, making the MNF highly favorable for optical sensing [21][22][23][24][25][26][27][28][29][30][31][32] and evanescent coupling between the MNF and other waveguides (e.g., a semiconductor [33,34], metal [35,36] nanowire or planar waveguide [37]) or a substrate [30,35,38,39]. Based on the high-efficiency evanescent coupling, a variety of optical components or devices (e.g., loop and knots resonators [40][41][42][43][44][45][46][47][48][49][50][51], lasers [52][53][54][55][56][57][58], and sensors [21][22][23][24][25][26][27]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation